Anion Channels and the Stimulation of Anthocyanin Accumulation by Blue Light in Arabidopsis Seedlings - Noh, Bosl (American Society of Plant Physiologists, 1998)
Activation of anion channels by blue light begins within seconds of irradiation in seedlings and is related to the ensuing growth inhibition. 5-Nitro-2-(3-phenylpropylamino)-benzoic acid (NPPB) is a potent, selective, and reversible blocker of these anion channels in Arabidopsis thaliana. Here we show that 20 μm NPPB blocked 72% of the blue-light-induced accumulation of anthocyanin pigments in seedlings. Feeding biosynthetic intermediates to wild-type and tt5 seedlings provided evidence that NPPB prevented blue light from up-regulating one or more steps between and including phenylalanine ammonia lyase and chalcone isomerase. NPPB was found to have no significant effect on the blue-light-induced increase in transcript levels of PAL1, CHS, CHI, or DFR, which are genes that encode anthocyanin-biosynthetic enzymes. Immunoblots revealed that NPPB also did not inhibit the accumulation of the chalcone synthase, chalcone isomerase, or flavanone-3-hydroxylase proteins. This is in contrast to the reduced anthocyanin accumulation displayed by a mutant lacking the HY4 blue-light receptor, as hy4 displayed reduced expression of the above enzymes. Taken together, the data indicate that blue light acting through HY4 leads to an increase in the amount of biosynthetic enzymes, but blue light must also act through a separate, anion-channel-dependent system to create a fully functional biosynthetic pathway.